Rynek wideo w Polsce - Grzegorz Fortuna (Images)
The development of VHS market in Poland can be roughly divided into two main periods: first (1980-1988) is the one when that area of pop culture first came into existence and shaped, second (1988-1992) is the "video boom" era. In the years 1980-1988 the video market developed thanks to the cunningness and resourfulness of a large number of people who succumbed to the magic of that new medium. They worked almost entirely illegally because the market was not being regulated by any legal norms and the cassettes that were being produced were of a very low quality. In the years 1988-1992 the VHS market was on a very high demand. Significant piracy-limiting legal norms were introduced and professional production and distribution companies began to play a larger role than before. Renting VHSs and watching movies on one's own TV set became a massive phenomenon. The article is an attempt to tell the unknown story of video-cassettes in Poland – methods of their dissemination, mechanisms of VHS market and influence on Polish audience.